PENGUATAN KARAKTER PEDULI LINGKUNGAN DI LINGKUNGAN MADRASAH IBTIDAIYAH AL-MURSYIDAH JONGGRONG MELALUI PROGRAM ADIWIYATA - Ivo Retna Wardani; Yeni Fitriya; Rohmad Rohmad (Lembaga Penelitian dan Pengabdian Masyarakat STIES Babussalam, 2026)
Strengthening students' environmentally conscious character within the madrasah (Islamic school) environment is implemented as part of the Adiwiyata program. This program aims to foster a sense of responsibility among the school community regarding environmental protection and management; consequently, it requires careful planning, a structured process for character reinforcement, and an analysis of supporting and inhibiting factors. This study employs a descriptive qualitative research method, with data collected through documentation, observation, and interviews. Data analysis was conducted using triangulation. The results indicate that: (1) activity planning involves reviewing the madrasah's vision and mission and designing environmentally oriented programs; (2) the process of strengthening environmentally conscious character is carried out by integrating environmental education into the curriculum, as well as through role modeling, habituation, and student discipline; and (3) supporting factors include stakeholder backing and well-structured activity programs, while inhibiting factors include the need for broader community support and a lack of adequate funding.